Icariside II, a PDE5 Inhibitor, Suppresses Oxygen-Glucose Deprivation/Reperfusion-Induced Primary Hippocampal Neuronal Death Through Activating the PKG/CREB/BDNF/TrkB Signaling Pathway - Xu, Fan; Lv, Chun; Deng, Yan; Liu, Yuangui; Gong, Qihai; Shi, Jingshan; Gao, Jianmei (Frontiers in Pharmacology, 2020)
Background: Ischemic stroke remains the leading cause of death and adult disability. Cerebral ischemic/reperfusion (I/R) injury is caused by ischemic stroke thereafter aggravates overwhelming neuronal apoptosis and even death. Of note, hippocampus is more susceptive to cerebral I/R injury than the other brain region. In this study, the effects and mechanism of icariside II (ICS II), a pharmacologically active compound exists in herbal Epimedii with previous study-proved as a phosphodiesterase 5 (PDE5) inhibitor, was investigated in vitro adopted the oxygen glucose deprivation/reoxygenation (OGD/R) cellular model in primary hippocampal neurons. Methods: Effects of ICS II on primary hippocampal neuronal impairment and apoptosis induced by OGD/R were examined by MTT, lactate dehydrogenase (LDH) release, TUNEL staining and flow cytometry, respectively. Expressions of memory-related signaling pathways were measured using Western blot analysis. The direct interaction between ICS II and PDE5 was further evaluated by molecular docking. Results: ICS II (12.5 μM, 25 μM, 50 μM) markedly abrogated OGD/R-induced hippocampal neuronal death as suggested by the increase in neurons viability and the decrease in cellular LDH release. Furthermore, ICS II not only effectively decreased the protein expression and activity of PDE5, restored the 3’5’-cyclic guanosine monophosphate (cGMP) level and its downstream target protein kinase G (PKG) activity, but also increased the phosphorylation of cAMP response element binding protein (CREB) level and expressions of brain derived neurotrophic factor (BDNF), tyrosine protein kinase B (TrkB). Mechanistically, the inhibitory effects of ICS II were abrogated by Rp-8-Br-cGMPS (Rp.) (a PKG inhibitor) or ANA-12 (a TrkB inhibitor), which further confirmed that the favorable effects of ICS II were attributed to its activation of the PKG/CREB/BDNF signaling pathways. Intriguingly, ICS II might effectively bind and inhibited PDE5 activity as demonstrated by relatively high binding scores (-6.52 kcal/mol). Conclusions: ICS II significantly rescues OGD/R-induced hippocampal neuronal injury. The mechanism is, at least partly, due to inhibition of PDE5 and activation of PKG/CREB/BDNF/TrkB signaling pathway. Hence it is thought that ICS II may be a potential naturally-PDE5 inhibitor to combat cerebral I/R injury.